Pelatihan Pembuatan Program Outbound Tim Building Bagi Guru MGMP PJOK Tingkat SD Se-Kota Kupang - Siagian, Fera Ratna Dewi; Boleng, Lukas Maria; Babang, Veramyta Maria Martha Flora; Ladjar, Maria Andriani Barek; Siahaan, Jurdan Martin (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
Team collaboration, commonly known as team building, is an essential aspect in the era of Society 5.0. Through collaboration, team members can create effective communication and cooperation. One way to train team building is through outbound programs. However, outbound programs are still not well known among PE teachers. Therefore, through this community service activity, the community service team offers a solution to introduce outbound programs while providing a means for teachers to develop their innovation and creativity. The program is titled "Training on Creating Outbound Team Building Programs for High School PE Teachers in the City of Kupang." This activity was attended by 20 teachers from various high schools in Kupang. The results of this activity include: 1) PE teachers gained new insights into various outbound programs that can enhance team building, 2) PE teachers practiced various outbound programs firsthand, gaining valuable experience, and 3) By the end of the activity, PE teachers were able to design outbound programs to enhance team building. In conclusion, the PE teachers acquired new skills in designing outbound programs that can improve team collaboration. As a result, PE teachers can organize outbound programs for students through intracurricular, co-curricular, and extracurricular activities.